(untitled) (Eurasian Research Bulletin, 2022)
This article addresses the issue of the chemical industry there are a number of organic wastes that can replace synthetic polymers. After processing this waste, it becomes an adhesive binder with good adhesion properties. In connection with this, it becomes necessary to study this problem, the solution of which is devoted to the article. The main purpose of the work is to substantiate and develop technologies for the production of polycondensates based on liquid distillation residues. In accordance with the above main goal of the study, the following tasks were formed and solved: Studied the condensation of the VAT residue of monoethanolamine. The chemical, physicomechanical properties of the resin, their application in various sectors of the national economy have been studied.